Relationship of Perceived Overqualification and Turnover Intention: The Role of Job Satisfaction and Transformational Leadership - Permatasari, Araminta; Nugroho, Sukmo Hadi (Universitas Brawijaya, Indonesia, 2024)
Employees with perceived overqualification have a strong need for self-actualization and development, which, if not met, can lead to frustration and increase turnover intention. This study examines the complex relationship between perceived overqualification and employee turnover intention, with job satisfaction as a mediating factor and transformational leadership as a moderating variable. This research type is quantitative, using a questionnaire with a Likert scale. Data was taken from 160 employees of startup marketplace companies in the Special Region of Jakarta who are members of Generation Z. The data sample was selected using a purposive sampling approach. The data processing results using SEM-PLS indicate that perceived overqualification positively predicts turnover intention, with this relationship partially mediated by decreased job satisfaction. It is also known that transformational leadership can weaken the relationship between job satisfaction and turnover intention but strengthen the relationship between perceived overqualification and job satisfaction. These findings provide an empirical concept that in carrying out commitments to manage employees with perceived overqualification (especially Generation Z), companies need to focus on channeling excess qualifications by setting a platform and developing leadership.